Testing of the N, P, and K nutrients in rice soil in the Kalawarat district of North Minahasa Regency - Kumolontang, Wiesje J.N.; Karamoy, Lientje Theffie; Rondonuwu, Jenny J.; Kawulusan, Rafli (Jurnal Agroekoteknologi Terapan, 2024)
The specific goals of the field and laboratory research on N, P, and K nutrient content tests in paddy soil in Kalawat District, North Minahasa Regency, are to increase the production of paddy rice plants by investigating and testing the nutrient contents of N, P, and K in rice field soil using a survey method with composite soil sampling that is tailored to the conditions of rice field soil for rice plants in the field. both at the top and bottom with In condition 1. On processed rice fields prepared for planting. 2. In rice fields where one-month-old rice has been sown. 3. In freshly harvested rice fields. Three composite soil samples were acquired for each paddy field soil condition for rice plants, and these samples were blended to create six soil samples (observations). The entire research project, from planning to report development, took eight months. The Paddy Soil Test Kit (PUTS) was used to collect qualitative data from soil samples collected in the field. Later, the soil samples were examined in the lab using the Kjeldhal method for N content, the Bray 1 method for P levels, and the spectrophotometric method for K levels. Tabular descriptive analysis is the method of data analysis that is employed. According to the study's findings, the nutrient content of the rice fields in Kalawat District, North Minahasa, N. is categorized as low to medium. Keywords: Rice plants, Paddy soil, N, P, and K. Abstrak Penelitian tentang Uji Kandungan Hara N, P dan K Pada Tanah Sawah Di Kecamatan Kalawat Kabupaten Minahasa Utara merupakan penelitian di Lapangan dan Laboratorium dengan tujuan khusus yang ingin dicapai dalam penelitian ini adalah Meningkatkan produksi tanaman padi sawah; dengan cara meneliti dan menguji kandungan hara Nitrogen, Fosfor dan Kalium pada tanah sawah, dengan menggunakan metode survei dengan pengambilan sampel tanah secara komposit disesuaikan dengan keadaan kondisi tanah sawah pada tanaman padi yang ada di lapangan.  Pada bagian atas dan bagian bawah dengan  Kondisi 1. Pada tanah sawah yang telah selesai diolah dan siap ditanami. Kondisi 2. Pada tanah sawah yang telah ditanami padi berumur 1 bulan. Kondisi 3. Pada tanah sawah yang baru selesai dipanen. Masing-masing kondisi tanah sawah untuk tanaman padi diambil 3 sampel tanah secara komposit kemudian dicampur sehingga diperoleh 6 Sampel tanah (pengamatan). Waktu penelitian selama 8 bulan dari persiapan sampai pembuatan laporan. Sampel tanah yang diperoleh di lapangan di analisis menggunakan Perangkat Uji Tanah Sawah (PUTS) sebagai data kualitatif dan di Laboratorium dianalisis Kadar N dengan menggunakan metode Kjeldhal; Kadar P dengan menggunakan metode Bray 1; Kadar K dengan menggunakan metode Spektrofotometri. Metode analisis data yang digunakan adalah analisis deskriptif secara tabelaris. Hasil dari penelitian ini  menunjukkan Kandungan Hara pada Lahan sawah di Kecamatan Kalawat Minahasa Utara N tergolong Rendah sampai sedang, P tergolong rendah hingga sedang dan K tergolong sedang. Kata kunci : N, P, K, Tanah Sawah, Tanaman Padi